Essential to increase the use of generics in Europe to maintain comprehensive health care? - Godman, Brian; Bennie, Marion; Baumgärtel, Christoph; Sović-Brkičić, Ljiljana; Burkhardt, Thomas; Fürst, Jurij; Garuoliene, Kristina; Gomes, Miguel; Markovic-Pekovic, Vanda; Martin, Andrew; et al. (Farmeconomia. Health economics and therapeutic pathways, 2012)
INTRODUCTION: Reforms have been introduced across Europe to increase prescribing efficiency with existing drugs. These include measures to lower prices of generics as well as increase their prescribing versus originators and patented products in a class or related class. This is essential to maintain comprehensive health care in Europe given continued pressures. The alternative is insufficient funds for new innovative drugs and increasing drug volumes with ageing populations. OBJECTIVE: To review the influence of measures and initiatives to increase the prescribing and dispensing of generics at low prices on ambulatory care prescribing efficiency. In view of this, provide guidance as authorities strive to introduce further reforms to meet their goals. METHODOLOGY: A narrative review of published papers combined with case histories. RESULTS: The different supply- and demand-side measures have reduced generic prices to as low as 2% to 3% of pre-patent loss prices in some cases as well as appreciably enhanced their utilisation. As a result, prescribing efficiency has increased without compromising care. In some cases, the reforms have led to expenditure actually falling despite appreciably increased volumes. CONCLUSIONS: Increasing use of generics at low prices will help maintain the European ideals of comprehensive and equitable health care. However, countries will continually need to learn from each other.